Absolute structure determination of compounds with axial and planar chirality using the crystalline sponge method1. Issue 7 (15th July 2015) - Yoshioka, Shota; Inokuma, Yasuhide; Hoshino, Manabu; Sato, Takashi; Fujita, Makoto
<x xml:space="preserve">Abstract</x> The absolute structure determination of compounds with axial and planar chirality obtained by recently developed asymmetric syntheses was achieved using the crystalline sponge method without using any reference compounds or synthetic modifications.